Dreams of a dark warrior - Cole, Kresley (The immortals after dark series, 2011)
Murdered before he could wed Regin the Radiant, warlord Aidan the Fierce seeks his beloved through eternity, reborn again and again into new identities, yet with no memory of his past lives. When Regin encounters Declan Chase, a brutal Celtic soldier, she recognizes her proud warlord reincarnated. But Declan takes her captive, intending retribution against all immortals - unaware that he belongs to their world.